2016
DOI: 10.1002/arch.21319
|View full text |Cite
|
Sign up to set email alerts
|

AN ODORANT‐BINDING PROTEIN INVOLVED IN PERCEPTION OF HOST PLANT ODORANTS IN LOCUST Locusta migratoria

Abstract: Locusts, Locusta migratoria (Orthoptera: Acrididae), are extremely destructive agricultural pests, but very little is known of their molecular aspects of perception to host plant odorants including related odorant-binding proteins (OBPs), though several OBPs have been identified in locust. To elucidate the function of LmigOBP1, the first OBP identified from locust, RNA interference was employed in this study to silence LmigOBP1, which was achieved by injection of dsRNA targeting LmigOBP1 into the hemolymph of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Amongst the OBPs in this group (Group D), only the olfactory function of Lo. migratoria OBP1, which may be involved in detecting plant volatiles, has been investigated so far (Zheng et al ., ; Li et al ., ). PameOBP1 and PameOBP2 may participate in general odorant reception, having been shown to have affinities with some plant volatiles in vitro (Li et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the OBPs in this group (Group D), only the olfactory function of Lo. migratoria OBP1, which may be involved in detecting plant volatiles, has been investigated so far (Zheng et al ., ; Li et al ., ). PameOBP1 and PameOBP2 may participate in general odorant reception, having been shown to have affinities with some plant volatiles in vitro (Li et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another leaf volatile, Z-3-Hexenol elicited a significantly higher POR percentage over solvent (Figure 2C). Z-3-Hexenyl acetate (HA) is sensed by antenna with high sensitivity based on electroantennogram responses 28. However, similar to paraffin oil, 5% HA was unable to stimulate palps extension (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have used the RNA interference (RNAi) technique to identify OBP functions in insects (Biessmann et al, 2010; Pelletier et al, 2010; Zhang et al, 2016). Moreover, it might be possible to link behavior to OBP(s) by gene silencing (He et al, 2011; Swarup et al, 2011; Deng et al, 2013; Li et al, 2016; Shorter et al, 2016; Lin et al, 2017). In fact, RNAi based studies have shown that OBPs are involved in the detection of oviposition attractants (Biessmann et al, 2010; Pelletier et al, 2010), plant volatiles (He et al, 2011; Li et al, 2016; Zhang et al, 2016), host molecules (Deng et al, 2013), in the survival of insects (He et al, 2011; Lin et al, 2017), and regulates mating behavior (Shorter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%